Dynamic Stresses Near the Working Surface from A Plane Wave - N.Duskaraev; Sh.R.Akhmedov; T.O.Juraev; U.X.Umedova (Genius Publishing Group, 2022)
The paper considers the reaction of a cylindrical layer located in a viscoelastic medium, when exposed to a transverse (longitudinal) seismic wave. It has been established that the maximum dynamic stress is 10-15% higher than the static one, and the wave numbers at which the maximum value is reached
Keywords: spherical shell; spherical protective domes; hesitation